9P21.3 locus; An Important Region in Coronary Artery Disease: A Panel Approach to Investigation of the Coronary Artery Disease Etiology - Omidi, Soodeh; Ebrahimzadeh, Fatemeh; Kalayinia, Samira (International Journal of Cardiovascular Practice)
Coronary artery disease (CAD) is a disease of major concern worldwide. It is the main cause of mortality in many societies and improving the understanding about the CAD mechanism, progression and treatment, is necessary. Recent discovery of genetic factors underlying CAD has improved our knowledge of the disease in support of well-known traditional risk factors. Genotype-environment interaction is known as the main risk factor. Loci on many different chromosomes have been identified as a risk factors that increase CAD susceptibility. Here we performed a comprehensive literature review pinpointing hotspot loci involved in CAD pathogenicity. The 9p21.3 locus is the most common region associated with CAD and its specific structure and function have been remarkable in many studies. Moreover, the variations in the 9p21.3 locus have been implicated in CAD patients in different populations around the world. According to conclusions from this the 9p21.3 locus can be the first point of focus in etiology investigations of CAD patients.